Labeling of proteins with 125I and experimental determination of its specific activity - Radicella, Renato; Caro, R. A.; Ciscato, V. A.; Giacomini, S. M. V. de; Quiroga, S. (Pergamon Press, 1975)
Fil: Radicella, Renato Comisión Nacional de Energía Atómica; Argentina